2011
DOI: 10.3109/0284186x.2011.602109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relationship between Hashimoto's thyroiditis and papillary thyroid cancer

Abstract: HT was definitely associated with PTC as was chronic inflammation with cancer in other locations. Interestingly, however, the coexistence of HT in PTC cases introduced favourable clinical outcomes compared with those of PTC without HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
92
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 18 publications
9
92
0
10
Order By: Relevance
“…Although it is not statistically significant, our study showed that, the TNM staging of PTC patients in HT group had a higher proportion of stage I than the PTC patients in non-HT group. These results were compatible with the literatüre and these results can be suggestive that the tumor's biological behavior is better in the case of HT or its due to the close follow-up of HT patients for thyroid disorders (3,6,9,14).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although it is not statistically significant, our study showed that, the TNM staging of PTC patients in HT group had a higher proportion of stage I than the PTC patients in non-HT group. These results were compatible with the literatüre and these results can be suggestive that the tumor's biological behavior is better in the case of HT or its due to the close follow-up of HT patients for thyroid disorders (3,6,9,14).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, many studies reported that PTC patients with HT is younger (6,8). This mismatch, may be due to the small number of PTC patients with HT in our study group.…”
Section: Discussionmentioning
confidence: 42%
“…The literature also describes other types of malignant lesions such as medullary carcinomas and even anaplastic thyroid cancer [21]. Generally, the percentages of PTC exceed those of FTC and medullary carcinoma [20][21][22].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Several analyses of surgical resection specimens have shown that PTC is frequently accompanied by HT. Interestingly, PTC with HT is associated with a lower rate of neck lymph node metastasis and has a better prognosis than PTC without thyroiditis in spite of increased incidence correlation [1][2][3][4][5][6][7][8][9][10]. In contrast, other studies conducted by fine-needle aspiration biopsy specimens and ultrasonographic findings have found no correlation between the incidences of these two diseases, with researchers insisting that HT does not increase the risk of thyroid…”
mentioning
confidence: 72%